Identification of a miRNA–mRNA Regulatory Networks in Placental Tissue Associated With Tibetan High Altitude Adaptation - Tenzing, Noryung; van Patot, Martha Tissot; Liu, Huifang; Xu, Qiying; Liu, Juanli; Wang, Zhuoya; Wang, Yanjun; Wuren, Tana; Ge, Ri-Li (Frontiers in Genetics, 2021)
The Tibetan population has lived and successfully reproduced at high altitude for many generations. Studies have shown that Tibetans have various mechanisms for protection against high-altitude hypoxia, which are probably due, at least in part, to placental adaptation. However, comprehensive in silico analyses of placentas in Tibetans are lacking. We performed a microarray-based comparative transcriptome analysis of 10 Tibetan women from Yushu, Qinghai, CHN (~3780 m) and 10 European women living in Leadville, CO, USA (~3100 m) for less than three generations. Expression of HIF-1α, STAT3, EGFR, HSP5A, XBP1 and ATF6A mRNA was less in the Tibetan placentas as compared with European placentas. A total of 38 miRNAs were involved in regulating these genes. Differentially expressed genes were enriched for HIF1α signaling pathways, protein processing in the endoplasmic reticulum, PI3K-AKT signaling pathways, and MAPK signaling pathways. Based on the transcriptome profiles, the Tibetan population was distinct from the European population; placental tissues from the Tibetan population are lacking hypoxic responses, and "passivation" occurs in response to hypoxic stress. These results provide insights into the molecular signature of adaptation to high altitudes in these two populations.